The concept of shared risk in public and private sector water security: a case study of Grabouw and the Elgin Valley, Western Cape, South Africa - Baleta, Hannah Francis (University of Cape Town, 2015)
Includes bibliographical references === This thesis investigates water risk in small-to medium-sized agro-processing companies and the public sector. Global interest in water management from the private sector has led to an increase in the development of water risk tools that are available to companies. Not only has the number of tools increased, but also the quality and form of these tools has been refined. Water risks are complex and extensive, and cannot be managed alone. Private sector interest in partnership and collaboration with other actors in managing water risk has increased as a result. The principal aim of this thesis is to investigate and explain the idea of shared water risk, using an adaptive theory process within a case study to investigate the understanding and knowledge of water risks among public and private actors. The study is informed by an assumption that if private and public interests are aware of the collective risks within a catchment, then sustainability of those business enterprises and public services, along with the protection and conservation of water resources may be possible. The case study is located in Grabouw and the Elgin Valley in the Theewaterskloof Local Municipality, Western Cape, South Africa. Private sector actors include agro-processing industries in the region, while the public sector includes local municipality officials and water resources management institutions such as the Catchment Management Agency and the Water Users Association. A conceptual framework of water risk and a sharing typology was developed from an analysis of interviews and the use of secondary sources of documents on the hydrology and socio-economic information on the catchment. The conceptual framework identifies the different water risks of the private and public sector, while the sharing typology indicates the progression of knowledge and understanding of private and public sector water risks, recognising that sharing does not take place in a single form. The framework and the typology together are intended to integrate an understanding of the theory and empirical data. Refinement of the framework and typology found that shared risk is especially pertinent in situations where systemic water risks affect the management of water and where that risk cannot be managed by individual companies or public sector authorities alone. The conceptual framework and typology identify the private and public sector exposure to risks, enabling actors to understand the scale and form of the respective risks in each sector. Where risks are not shared, the process of investigating the knowledge and understanding of risks helps to identify the complexity of the system. Contributions of this thesis include the use of risk as a common language to help bring together diverse sectors, especially when participatory decision-making is required. Not only the technical aspects of water supply and sanitation, but the wider social and environmental factors need to be considered as well. Understanding water security as a risk enables a wider and more diverse stakeholder group. The thesis concludes that collaboration and adaptive management need to be informed by knowledge and understanding of the complexity of risks within the catchment by multiple stakeholders.